Comparison of Keyword Search Techniques with Respect to Electronic Health Records - Prachi Gurav; Sanjeev Panandikar (ACHSM, 2021)
As the world progresses towards automation, manual search for data from large databases also needs to keep pace. When the database includes health data, even minute aspects need careful scrutiny. Keyword search techniques are helpful in extracting data from large databases. There are two keyword search techniques: Exact and Approximate. When the user wants to search through EHR, a short search time is expected. To this end, this work investigates Metaphone (Exact search) and Similar_Text (approximate search) Techniques. We have applied keyword search to the data, which includes the symptoms and names of medicines. Our results indicate that the search time for Similar_text is better than for Metaphone.